2020
DOI: 10.1111/vsu.13510
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of optical coherence tomography for assessing surgical margins of canine soft tissue sarcomas in observers of different specialties

Abstract: Objective: To determine the diagnostic accuracy of optical coherence tomography (OCT) to assess surgical margins of canine soft tissue sarcoma (STS) and determine the influence of observer specialty and training. Study design: Blinded clinical prospective study. Animals: Twenty-five dogs undergoing surgical excision of STS. Methods: In vivo and ex vivo surgical margins were imaged with OCT after tumor resection. Representative images and videos were used to generate a training presentation and data sets. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…These images show tissue microstructure comparable to that seen on a low‐magnification histology slide 12‐16 . The images can be interpreted with a high diagnostic accuracy by observers in various specialties after a short standardized training module, and can accurately differentiate normal tissues from canine soft tissue sarcoma and human breast cancer 10‐15,17,18 . In light of these findings, the authors suspect that OCT could have applications in guiding pathology sampling in excised tumour specimens to aid in surgical margin assessment.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…These images show tissue microstructure comparable to that seen on a low‐magnification histology slide 12‐16 . The images can be interpreted with a high diagnostic accuracy by observers in various specialties after a short standardized training module, and can accurately differentiate normal tissues from canine soft tissue sarcoma and human breast cancer 10‐15,17,18 . In light of these findings, the authors suspect that OCT could have applications in guiding pathology sampling in excised tumour specimens to aid in surgical margin assessment.…”
Section: Introductionmentioning
confidence: 72%
“…OCT evaluation of the surgical margin in this report had a high sensitivity and moderate specificity, allowing it to identify incomplete excision in four specimens when standard sectioning did not identify residual MCT cells. OCT is an imaging technology that is easy to learn and interpret with a high degree of accuracy 14,18 . A study currently under peer review has identified that a short training module was sufficient to teach clinicians of multiple specialties and experience levels how to interpret OCT imaging to discern canine soft tissue sarcoma from normal tissues with good accuracy 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Another recent study utilized OCT tissue appearance to train observers to determine the diagnostic accuracy of OCT for surgical margin evaluation for canine STS. 6 It reported a diagnostic accuracy of 91.4% of in vivo images and 89.5% of ex vivo images. 6 Observer accuracy may be further improved with development of objective criteria, using image processing to aid interpretation, and using machine or deep learning algorithms.…”
Section: Introductionmentioning
confidence: 98%
“…6 It reported a diagnostic accuracy of 91.4% of in vivo images and 89.5% of ex vivo images. 6 Observer accuracy may be further improved with development of objective criteria, using image processing to aid interpretation, and using machine or deep learning algorithms. The primary aim of this study was to assess tissue depth (TD) with imaging processing of four tissue types from OCT surgical margin images of canine STS resections.…”
Section: Introductionmentioning
confidence: 98%